Expanded Animation and Memory - Rezaei Salarnia, Zahra (Auckland University of Technology, 2023)
The research discusses the embodiment of my childhood memories through expanded animation’s materiality, temporality, and space. It seeks alternative approaches for the production and representation of animation, to provoke multisensory perception of my subjective recollections. The project’s heuristic methods synthesise theoretical, practical, and embodied knowledge via reflective practices. The theories of memory, time, drawing, animation, and multisensory perception, and the artistic practices of William Kentridge, Yuri Norstein, and Emy Kravitz guided the production of a multi-channel hybrid installation, No. 28. Made of hand-drawn animations, No. 28 materialises the nature of my memories in charcoal drawings, the animation’s rhythm, and the installation space, provoking atmospheric and sensory experiences.